ANALISIS KELELAHAN ELEMEN TENDON STRUKTUR BANGUNAN LEPAS PANTAI BERDASARKAN SPEKTRUM BEBAN DINAMIS GELOMBANG - Husain, Syahril
The life time of an offshore structure can be predicted by fatigue analysis of its critical parts. The concepts for fatigue analysis are fracture mechanics and acumulative damage by Miner's law.This thesis uses the first concept. Assuming of this concept is in the, material exists initial crack and the crack propagates caused by cycel loading. That material is fatigue, if its fracture toughness is reached. The part of structure that analyzed is Tendon of Tension Leg Platform. Tendon gets loading caused by moving of its main structure. Responses of main structure are calculated by frequensi domain and the exciting force is wave force only Results of this analysis show that the life time of the structure are influenced by dimension of main structure, crack geometry and cross section of tendon.